A microfluidic competitive immuno-aggregation assay for high sensitivity cell secretome detection. (3rd April 2018) - Liu, Fan; KC, Pawan; Ni, Liwei; Zhang, Ge; Zhe, Jiang
ABSTRACT: We report a high-sensitivity cell secretome detection method using competitive immuno-aggregation and a micro-Coulter counter. A target cell secretome protein competes with anti-biotin-coated microparticles (MPs) to bind with a biotinylated antibody (Ab), causing decreased aggregation of the functionalized MPs and formation of a mixture of MPs and aggregates. In comparison, without the target cell secretome protein, more microparticles are functionalized, and more aggregates are formed. Thus, a decrease in the average volume of functionalized microparticles/aggregates indicates an increase in cell secretome concentration. This volume change is measured by the micro-Coulter counter, which is used to quantitatively estimate the cell secretome concentration. Vascular endothelial growth factor (VEGF), one of the key cell secretome proteins that regulate angiogenesis and vascular permeabilization, was used as the target protein to demonstrate the sensing principle. A standard calibration curve was generated by testing samples with various VEGF concentrations. A detection range from 0.01 ng/mL to 100.00 ng/mL was achieved. We further demonstrated the quantification of VEGF concentration in exogenous samples collected from the secretome of human mesenchymal stem cells (hMSCs) at different incubation times. The results from the assay agree well with the results of a parallel enzyme-linked immunoabsorbent assay (ELISA) test, indicating the specificity and reliability of the competitive immuno-aggregation assay. With its simple structure and easy sample preparation, this assay not only enables high sensitivity detection of VEGF but also can be readily extended to other types of cell secretome analysis as long as the specific Ab is known.